Comparison of ultrasonic pachymetry and Fourier-domain optical coherence tomography for measurement of corneal thickness in dogs with and without corneal disease. (December 2018) - Hoehn, A.L.; Thomasy, S.M.; Kass, P.H.; Horikawa, T.; Samuel, M.; Shull, O.R.; Stewart, K.A.; Murphy, C.J.
Highlights: Corneal thickness measured by ultrasonic pachymetry (Pachette 3 & Accupach VI) and two FD-OCT methods were compared. Corneal thickness varied predictably depending on age, weight, and corneal disease status. The Pachette 3 produced higher corneal thickness measurements than the other three methods. Endothelial disease can markedly increase corneal thickness, sometimes beyond the measurable limit of pachymetry devices. Abstract: Several ultrasonic and Fourier-domain optical coherence tomography (FD-OCT) pachymeters are used to measure corneal thickness in canine patients and research subjects. This study assessed the reliability of and consistency between two ultrasonic pachymetry (USP) devices, Pachette 3 and Accupach VI, as well as automated and manual measurements obtained using FD-OCT in dogs with and without corneal disease. Corneal thickness measurements were compiled from 108 dogs and analyzed using mixed effects linear regression, with Bonferonni adjustments for post-hoc comparisons, to determine the effects of age, weight and disease state. Data are presented as predicted mean ± standard error. Canine corneal disease can result in marked increases in thickness that frequently exceed the upper limits of measurement of some pachymetry devices developed for human use. In this study, the corneas of dogs with endothelial disease or injury frequently exceeded the upper limits of quantitation of 999 and 800 μm for the Accupach VI and automated FD-OCT pachymeters, respectively. Using values <800 μm, the Pachette 3 generated significantly greater values for central corneal thickness (CCT) than the Accupach VI, manual FD-OCT and automated FD-OCT at 625 ± 7.0, 615 ± 7.2, 613 ± 7.2, and 606 ± 7.4 μm respectively ( P  < 0.001). Of the two devices where measurements >1000 μm were obtained, manual FD-OCT demonstrated less variability than the Pachette 3. Corneal thickness increased linearly with age and weight with an increase of 6.9 ± 1.8 μm/year and 1.6 ± 0.8 μm/kg body weight ( P <  0.005 and P  = 0.038, respectively).